Survival and reinfection rates of SCTLD-affected corals treated in situ with amoxicillin - Neely, Karen L.; Nowicki, Robert J.; Dobler, Michelle A.; Toth, Kathryn A.; Macaulay, Kevin A.; Gallagher, Sydney M. (Frontiers in Marine Science, 2025)
The unprecedented mortality to Caribbean corals caused by stony coral tissue loss disease (SCTLD) led to the use of an in-water medicine applied directly to disease lesions. This topical amoxicillin paste is highly effective in halting lesions and has been used on tens of thousands of wild corals since 2019, but long-term survival rates of treated corals as well as the frequency of potential reinfections remained speculative. We fate-tracked thousands of corals treated for SCTLD in the Florida Keys across numerous species and two habitats (inshore patch reefs and offshore spur and groove) every two months, assessing health condition and providing additional treatments if necessary. After three years, 84% of corals remained alive. Inshore corals had higher survival rates than offshore corals, and there were species-specific differences in survival, with the boulder corals Montastraea cavernosa and Orbicella faveolata having higher survivorship than brain coral species. Across all treated corals, 36% remained disease-free for at least one year after the initial treatment, and an additional 18% remained disease-free if any new lesions were treated within three months after the initial treatment. Reinfection rates were influenced by both habitat and species, with inshore corals more likely to remain disease-free than offshore corals. Among the species assessed, Montastraea cavernosa was the most likely to remain disease free, while the brain corals Diploria labyrinthiformis and Colpophyllia natans were the most prone to reinfection. These measurements can help guide expectations for disease intervention projects, including survival estimates if corals are regularly visited, as well as predictions of survivorship if diseased corals are visited only once or twice.